PERAN STRATEGIS KEPALA SEKOLAH DALAM MENDUKUNG GURU MENERAPKAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Kartikawati, Eni; Darmuki, Agus; W., Sri Surachmi (INOPENDAS: Jurnal Ilmiah Kependidikan, 2025)
This study aims to describe the strategic role of the principal in supporting the implementation of differentiated learning at SD Negeri 4 Truwolu. The research method used is qualitative with a case study approach. Data collection was carried out through in-depth interviews with the principal and teachers, classroom observations, and document analysis. The results of the study indicate that the principal at SD Negeri 4 Truwolu. has a significant strategic role in supporting the implementation of differentiated learning. This role includes dimensions as a learning leader, professional development facilitator, collaborative culture builder, and monitor and evaluator. Several effective leadership strategies were identified, including open communication, teacher empowerment, and distributed leadership development. Differentiated learning has challenges, such as limited resources and differences in teacher capacity. The leadership of the principal at SD Negeri 4 Truwolu. has been shown to have a positive impact on the practice of differentiated learning, increasing teacher motivation and skills, and contributing to improving the quality of learning and student learning outcomes.